Effects of 15-Acetyl-deoxynivalenol (15-ADON) and Diacetoxyscirpenol (DAS) Mycotoxins on Tribolium castaneum - Toth, Mollie; Nguyen, Valerie; Scully, Erin (My University, 2018)
Two major threats to stored products in the United States and throughout the world are stored product insects and contamination from mycotoxins, which are secondary metabolites produced by fungi, such as Fusarium spp. (Glenn, 2007). Although stored product insects are not associated with negative health impacts when consumed by humans or animals, mycotoxins can negatively impact fertility, reproductive health, growth and development, particularly in livestock (Brake, 1999). Unfortunately, it is difficult to remove mycotoxins from contaminated products and most products have to be destroyed. However, stored product insects routinely feed on products contaminated by mold and may posses detoxification enzymes that could be exploited by the food industry to degrade mycotoxins. To determine whether Tribolium castaneum (red flour beetles) may have resistance to mycotoxins commonly encountered in stored products, such as 15-acetyl-deoxynivalenol (15-ADON) and diacetoxyscirpenol (DAS), we performed bioassays using 10-fold serial dilutions of both purified toxins independently and measured life history parameters, including mortality rates, growth rates, and progeny production. These parameters were compared to insects fed on a control diet to determine whether mycotoxins negatively impacted red flour beetle adults. This allows for an understanding of how individual mycotoxins influence the insects rather than their combinations seen in naturally contaminated mold (Guo, 2014).The results showed no significant impact on any of the life history parameters from the 15-ADON mycotoxin; however, the DAS showed a significant impact on growth rates and progeny production. Furthering the study of the resistance of red flour beetles to mycotoxins may allow us to discover novel enzymes that could be used to degrade mycotoxins contaminating grain, allowing it to be used as animal food and reducing post-harvest losses.
Keywords: Fall 2018